On related vector fields of capillary surfaces - Afet K. Özok (International Journal of Mathematics and Mathematical Sciences)
In this paper, some necessary and sufficient conditions are given for the related vector fields of capillary surfaces to be Killing, conformal Killing, and homothetic conformal Killing vectors in the n-dimensional domain Ω, and a construction of capillary surfaces is also given by means of the related vector fields.